University of Pennsylvania Radiocarbon Dates, VIII - Stuckenrath, Jr. Robert (1965)
i.a. Iran: Ziwiyeh; Iraq: Arpachiyah, Nippur, Tell es-Siwan, Ur; Turkey: Alaca Hüyük, Çatal Hüyük, Can Hasan, Gordion; Jordan: El-Jib, Tell es-Sa‛idiyeh.